STUDY OF DOSE DISTRIBUTION IN INHOMOGENEOUS PHANTOM USING MONTE CARLO SIMULATION FOR PHOTON BEAM - Cantia Paradita Dealuma, Niluh
Radiotherapy is used to stop the growth of cancer cells, yet normal tissue around cancer cells is at risk of radiation exposure. Therefore, simulation using the Monte Carlo method is needed to find out the distribution of doses received by patients. The study aimed to use the Monte Carlo method to determine the effect of inhomogeneous tissue on Percentage Depth Dose (PDD) and dose profile. The research used PRIMO software by modeling the Clinac 2100 Varian linear accelerator head in 6 MV photon beam mode. The phantoms were a homogeneous phantom composed of water and inhomogeneous phantoms consisted of water – bones, water – lungs, and water – bones – lungs with 5 × 5 cm2 and 10 × 10 cm2 field sizes. Each simulation took 4 – 10 hours, depending on the parameters used. The uncertainty was obtained in the range of 0,48% – 1,59% for PDD and 1.36% – 3.00% for dose profile. In PDD, it was seen that there was a change in the absorbed dose when it reached the inhomogeneous slab. For all phantoms unless the water-bone phantom with a field size 5 x 5 cm2, there are increasing absorbed dose of 0.15% – 1.86% in the region before the bone. Meanwhile, when PDD reached the lung slab, the dose decreased by 2.27% – 4.74%. Then, the results of the dose profile showed that the greater the depth of the phantom, the lower the dose profile curve. The lung slab gave the most outstanding value for flatness and penumbra, but the dose profile parameter values for the bone slab were not significantly different compared to other slabs. From the PDD, it can be concluded that the heterogeneous slabs impacted the dose distribution. However, the dose profile still needs further study to determine the effect of the heterogeneous slabs.